The work trajectories of married Canadian immigrant women, 2006-2019 - Ana M. Ferrer; Annie Pan; Tammy Schirle (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2022)
The behaviour of married immigrant women regarding fertility and labour markets is an essential piece to understand the economic and cultural integration of immigrant households. However, the contribution of married immigrant women to the Canadian labour market was - until recently - considered of secondary importance and their labour market choices studied within a framework of temporary attachment to the labor force. Recent research, however, finds that a significant fraction of married immigrant women make labor supply decisions (and face barriers) similar to those of native-born married women. We show that this is the case in Canada as well, by estimating the progress of immigrant women over the 2000s. We use traditional measures of labour market attachment, such as participation, employment and wages, but also novel measures of labour market dynamics, such as transitions across labour market states. Differences in transition rates can reveal higher fragility of work for immigrant women, or reveal the extent to which immigrant women respond to family income shocks - the added worker effect. Results show that immigrant women are less likely to transition into employment - more likely to transition out of employment to either unemployment or inactivity - and more likely to respond to income shocks than the Canadian born. There is evidence of a gradual convergence with years spent in Canada to the outcomes of the Canadian born, which is much slower for immigrant women than immigrant men.
Keywords: 330; Migranten; Frauen; Ehe; Erwerbstätigkeit; Lohn; Arbeitsmarktintegration; Kanada